2021
DOI: 10.1016/j.ijid.2020.11.155
|View full text |Cite
|
Sign up to set email alerts
|

Increasing SARS-CoV-2 RT-qPCR testing capacity by sample pooling

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 16 publications
(8 reference statements)
2
31
0
Order By: Relevance
“…Results from this retrospective study are consistent with recent reports confirming an insignificant effect on the false negative rate for pools of similar size; additionally, our average CT value shifts were precise [14,15]. Probit analysis is applicable to the bimodal output of RT-qPCR for LoD analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Results from this retrospective study are consistent with recent reports confirming an insignificant effect on the false negative rate for pools of similar size; additionally, our average CT value shifts were precise [14,15]. Probit analysis is applicable to the bimodal output of RT-qPCR for LoD analysis.…”
Section: Discussionsupporting
confidence: 92%
“…There can be no doubt that, in principle, RT-PCR in general and RT-qPCR in particular, are technologies eminently suitable for fast, accurate, reliable and high throughput molecular diagnostic testing, especially when employed creatively, for example by pooling samples [ 98 ]. RT-qPCR has proven its proficiency by having been the benchmark diagnostic technology for the identification of numerous pathogens, including viruses, for many years.…”
Section: Discussionmentioning
confidence: 99%
“…al. (2020) where they concluded that pooling of 5 samples is sufficient to detect the presence of SARS-CoV-2, especially when pooled in pre-RNA extraction phase (Alcoba-Florez et al, 2020; Volpato et al, 2020). However, this is in contrary to Yelin et.…”
Section: Discussionmentioning
confidence: 99%